Method for producing a laminate and use of a laminate for producing a battery housing

Through the lamination process of metal substrate and composite film, combined with adhesive and lubricating layer, the problems of numerous steps in the battery shell manufacturing process, high costs and poor film consistency in the prior art are solved, and the maximum depth drawing is achieved The battery case with a depth of 200mm is manufactured, which avoids composite film breakage and peeling defects, and improves the acid and alkali resistance and processing performance of the battery case.

CN119261219APending Publication Date: 2025-01-07JIANGSU DONGYANG STEEL SHEET NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410739712.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-06
Filing Date
2024-06-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing hard-pack battery shell manufacturing process has many steps, high costs and poor film consistency, so it is impossible to produce a battery shell with a depth of more than 120mm without causing composite film breakage and peeling defects.

Method used

Laminated with a metal substrate with a thickness of 0.12mm to 2.0mm with a composite film, which includes an adhesive layer and a polyolefin layer, is laminated and insulated from 100°C to 180°C, combined with an adhesive and a lubricating layer. , ensure the adhesion and tensile resistance of the laminated material, and avoid fracture and peeling of the composite film.

Benefits of technology

A drawing forming process with a maximum drawing depth of 200mm is achieved, which avoids composite film breakage and peeling defects, and improves the acid and alkali resistance and processing performance of the battery case.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119261219A_ABST
    Figure CN119261219A_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing a laminate and to the use of a laminate for producing a battery case, the method comprising taking a metal substrate (10); a composite film (20) is taken, the composite film comprises a bonding layer (21) and a polyolefin layer (22), at least one surface of the metal base material is covered with the composite film, and the face, provided with the bonding layer, of the composite film faces the metal base material; performing lamination; after the lamination is finished, preserving heat; and cooling. According to the method for manufacturing the laminated material provided by the invention, the laminated material for manufacturing the battery shell can be obtained, and the obtained laminated material can adapt to a deep drawing process with the deep drawing depth of 120-200 mm and does not have the defect of film breakage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for producing a laminated material and also to use of the laminated material for producing a battery casing. Background Art

[0002] The hard pack battery case is the carrier of the power battery, used to carry all components such as the plates, separators, and electrolytes. It is required to have good acid and alkali resistance, high strength, and good processability, and is mainly used to protect the battery from damage when it is hit or squeezed by the outside world. With the development of science and technology, people are eager to get high-capacity batteries. The same type of battery can obtain a larger capacity by increasing the volume, which requires increasing the volume of the battery case.

[0003] When a large-volume hard-pack battery case is produced by deep drawing, the existing process first draws the metal substrate to obtain a battery case blank, and then coats the battery case blank with a film. This process has many steps, high costs, and poor consistency of the coating process. There are also processes that coat the battery case before forming it, but only a small depth of drawing can be performed, and a battery case with a drawing depth greater than 120mm and the coated film is not broken cannot be produced. Summary of the invention

[0004] The object of the present invention is to provide a method for manufacturing a laminated material, which is capable of manufacturing a laminated material that is adapted to a deep drawing process with a maximum drawing depth of 200 mm.

[0005] The present invention provides a method for manufacturing a laminated material, comprising the following steps: taking a metal substrate with a thickness of 0.12 mm to 2.0 mm; taking a composite film, the composite film comprising an adhesive layer and a polyolefin layer, covering the composite film on at least one surface of the metal substrate, and making the side of the composite film provided with the adhesive layer face the metal substrate, the elongation at break of the polyolefin in the polyolefin layer being 300% to 800%; and forming the composite film at a temperature of 100° C. to 180° C. and a pressure of 0.1 N / mm 2 Up to 10N / mm 2 lamination under the conditions of 0.001 second to 1 second; after lamination, heat preservation, maintaining the heat preservation temperature above 80°C for more than 1 second; and cooling, wherein the temperature is controlled below 60°C and maintained for more than 2 seconds.

[0006] The present invention selects the material composition of the composite film and matches it with the above-mentioned laminate material manufacturing process, so that the laminate material can adapt to the drawing process with a maximum drawing depth of 200 mm and avoid the defects of composite film breaking and peeling from the metal substrate.

[0007] In another exemplary embodiment of the method for manufacturing a laminated material, before the step of covering the composite film on at least one surface of the metal substrate, the method further includes the following steps: applying an adhesive to at least one surface of the metal substrate to be covered by the composite film, wherein the adhesive is one or more of an epoxy adhesive, a polyurethane adhesive, and an acrylic adhesive, thereby improving the bonding force between the composite film and the metal substrate.

[0008] In another exemplary embodiment of the method for manufacturing a laminated material, after the cooling step, the method further includes the following steps: heating at a temperature of 80° C. or higher for more than 1 second, wherein the heating is performed by electric heating, hot air heating, or roller heating. This eliminates the stress difference of the composite film in the film thickness direction, reduces the crystallinity of the resin in the composite film, and thus improves the processing performance of the laminated material.

[0009] In another exemplary embodiment of the method for manufacturing a laminate, the adhesive layer comprises one or more of EVA and its modifications, EAA and its modifications, polyolefins containing maleic anhydride, and polyesters containing maleic anhydride, thereby facilitating reliable bonding between the polyolefin layer and the metal substrate.

[0010] In another exemplary embodiment of the method for manufacturing a laminated material, the thickness of the composite film is 17.5 μm to 150 μm, thereby facilitating the processability of the laminated material.

[0011] In another exemplary embodiment of the method for manufacturing a laminated material, the composite film further includes a lubricating layer, the lubricating layer comprising a polyolefin and a lubricant. The lubricating layer is formed on the side of the polyolefin layer away from the adhesive layer. In each composite film, the thickness ratio of the lubricating layer, the polyolefin layer and the adhesive layer is 3:4:3 to 1:8:1. This facilitates the rolled composite film to be non-adhesive during the lamination process and is easy to unwind, preventing the surface of the composite film from being damaged due to adhesion.

[0012] In another exemplary embodiment of the method for manufacturing a laminated material, the composite film further comprises a barrier layer. The barrier layer has a thickness of 5 μm or more. The barrier layer has an air permeability of 5 ml (m 2 ·day·Mpa) and is formed between the polyolefin layer and the lubricating layer. This gives the laminate a strong barrier property to prevent small molecules in the battery electrolyte from penetrating to the outside.

[0013] In another exemplary embodiment of the method for manufacturing a laminated material, the polyolefin contained in the polyolefin layer and the lubricating layer is the same and is selected from one or more of PP and PE, and the air permeability is 5 ml (m 2The resin with a density below 1000 ·day·Mpa is ethylene-vinyl alcohol copolymer. This helps to improve the compatibility of the lubricating layer and the polyolefin layer, so that the lubricating layer and the polyolefin layer are closely combined without peeling, and the laminated material is prevented from stratification in the subsequent deep drawing process, which is beneficial to improve the product quality of the laminated material.

[0014] In another exemplary embodiment of the method for making a laminated material, the composite film further comprises a PET layer. The PET layer is coated on the side of the polyolefin layer facing away from the adhesive layer, thereby making the laminated material scratch-resistant.

[0015] In another exemplary embodiment of the method for manufacturing a laminated material, the PET layer and the polyolefin layer are connected by an adhesive, thereby achieving a strong bond between the PET layer and the polyolefin layer.

[0016] In another exemplary embodiment of the method for manufacturing a laminated material, before the composite film is coated on the metal substrate, the side of the composite film facing away from the adhesive layer is attached to a substrate film, and the composite film is cut into continuous and / or discontinuous film blocks by a die-cutting die while keeping the substrate film intact. After the metal substrate is coated with the film block, a portion of the metal substrate is exposed to facilitate subsequent operations such as welding.

[0017] In another exemplary embodiment of the method for manufacturing a laminated material, the substrate film is a release PET, a release paper or a release nonwoven fabric.

[0018] In another exemplary embodiment of the method for manufacturing a laminated material, the metal substrate is selected from one of an untreated aluminum plate, an aluminum plate pre-treated with Ti / Zr, an aluminum plate treated with Cr, an aluminum plate treated with CP, an aluminum plate treated with hot water modification, an anodized aluminum plate and a surface-treated steel plate, and the surface-treated steel plate is a steel plate obtained by a combination of one or more surface treatment processes selected from electroplating, Ti / Zr treatment, Cr treatment, CP treatment, hot water modification and anodizing.

[0019] In a specific embodiment, the thickness of the metal substrate can be 0.12 mm or 2 mm, and the metal substrate can be selected from one of untreated aluminum plate, aluminum plate pre-treated with Ti / Zr, aluminum plate treated with Cr, aluminum plate treated with CP, aluminum plate treated with hot water modification, aluminum plate treated with anodizing, and steel plate treated with surface treatment, and a laminated material can be obtained, and the obtained laminated material can adapt to the drawing process with a maximum drawing depth of 200 mm and avoid the defects of composite film breaking and peeling from the metal substrate. In a specific embodiment, the lamination temperature is 100°C or 180°C, and a laminated material can be obtained, so that the laminated material can adapt to the drawing process with a maximum drawing depth of 200 mm and avoid the defects of composite film breaking and peeling from the metal substrate.

[0020] In a specific embodiment, the lamination pressure is 0.1 N / mm 2 or 10N / mm 2 A laminated material can be obtained, and the obtained laminated material can adapt to a drawing process with a maximum drawing depth of 200 mm and avoid defects such as fracture of the composite film and peeling off from the metal substrate.

[0021] In a specific embodiment, a laminated material can be obtained by using a lamination time of 0.001 second or 1 second. The obtained laminated material can adapt to a drawing process with a maximum drawing depth of 200 mm and avoid defects such as composite film breakage and peeling from the metal substrate.

[0022] In a specific embodiment, the insulation temperature is maintained at 80° C. to obtain a laminated material, which can adapt to a drawing process with a maximum drawing depth of 200 mm and avoid defects such as composite film breakage and peeling from the metal substrate.

[0023] In a specific embodiment, a laminated material can be obtained by adopting a holding time of 1 second, so that the laminated material can adapt to a drawing process with a maximum drawing depth of 200 mm and avoid defects such as fracture of the composite film and peeling off from the metal substrate.

[0024] In a specific embodiment, the temperature in the cooling step is controlled at 60° C., and a laminated material can be obtained. The obtained laminated material can adapt to a drawing process with a maximum drawing depth of 200 mm and avoid defects such as fracture of the composite film and peeling off from the metal substrate.

[0025] In a specific embodiment, the adhesive layer can be made of EVA, polyethylene modified EVA, polypropylene modified EVA, EAA, polyethylene modified EAA, polypropylene modified EAA, polypropylene containing maleic anhydride, polyethylene containing maleic anhydride, polybutene containing maleic anhydride, polyethylene terephthalate containing maleic anhydride, polybutylene terephthalate containing maleic anhydride, etc., all of which can be used to obtain laminated materials. The obtained laminated materials can adapt to the drawing process with a maximum drawing depth of 200 mm and avoid the defects of composite film breakage and peeling from the metal substrate.

[0026] In a specific embodiment, the thickness ratio of the lubricating layer, the polyolefin layer and the adhesive layer is 1:8:1, and a laminated material can be obtained. The obtained laminated material can adapt to a drawing process with a maximum drawing depth of 200 mm and avoid defects such as breakage of the composite film and peeling off from the metal substrate.

[0027] The present invention also provides a use of the laminated material manufactured according to the above method for manufacturing a battery casing.

[0028] In another exemplary embodiment of the use of the manufactured laminated material for manufacturing a battery housing, the laminated material is used to manufacture a battery housing by a deep drawing process. The deep drawing depth of the deep drawing process is 120 mm to 200 mm. In the forming process with a drawing depth of 120 mm to 200 mm, the laminated material manufactured by the method of the present invention is used to manufacture a battery housing, and the composite film is well attached to the metal substrate without showing defects of fracture and peeling. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The following drawings are only used to schematically illustrate and explain the present invention, and do not limit the scope of the present invention.

[0030] Figure 1 A flow chart of an illustrative embodiment of a method of making a laminate.

[0031] Figure 2 A schematic structural diagram of an exemplary embodiment of the obtained laminated material.

[0032] Figure 3 The schematic diagram of the structure of another exemplary embodiment of the obtained laminated material is shown in FIG.

[0033] Figure 4 The schematic diagram of the structure of another exemplary embodiment of the obtained laminated material is shown in FIG.

[0034] Figure 5 It is a schematic diagram for explaining the cutting of a composite film by a die-cutting die.

[0035] Description of symbols

[0036] 10Metal substrate

[0037] 20 composite film

[0038] 21 Adhesive layer

[0039] 22 Polyolefin layer

[0040] 23 Lubrication layer

[0041] 24 PET layers

[0042] 25 barrier layers

[0043] 26 membrane blocks

[0044] 30 substrate film

[0045] 40 die cutting mold

[0046] F feeding direction. DETAILED DESCRIPTION

[0047] In order to have a clearer understanding of the technical features, purposes and effects of the invention, the specific embodiments of the present invention are now described with reference to the accompanying drawings. The same reference numerals in the drawings represent components with the same structure or similar structures but the same functions.

[0048] In this document, “exemplary” means “serving as an example, instance or illustration”, and any diagram or implementation described in this document as “exemplary” should not be interpreted as a more preferred or more advantageous technical solution.

[0049] In order to simplify the drawings, each figure only schematically shows the parts related to the present invention, which do not represent the actual structure of the product.

[0050] Figure 1 The present invention is a flow chart of an exemplary embodiment of a method for manufacturing a laminated material. The laminated material prepared according to the method is used, for example, to manufacture a battery housing. Further, the laminated material prepared according to the method is used, for example, to manufacture a battery housing by a deep drawing process with a drawing depth of 120 mm to 200 mm.

[0051] See also Figure 1 The present invention provides a method for manufacturing a laminated material, comprising the following steps S102 to S110.

[0052] S102: Take a metal substrate with a thickness of 0.12 mm to 2.0 mm. The metal substrate may be, for example, aluminum, steel, etc. In an exemplary embodiment, the thickness of the metal substrate is 1 mm. In other exemplary embodiments, the thickness of the metal substrate may be other values ​​between 0.12 mm and 2.0 mm. The metal substrate may be, for example, an untreated aluminum plate, an aluminum plate pre-treated with Ti / Zr, an aluminum plate treated with Cr, an aluminum plate treated with CP, an aluminum plate treated with hot water, an anodized aluminum plate, and a surface-treated steel plate, which provide high strength and good processability for the hard-pack battery casing. The treatment process of the metal substrate can also improve the bonding strength between the metal substrate and the coating. The treatment process of the above metal substrate is well known to those skilled in the art, wherein the Ti / Zr treated aluminum plate is an aluminum plate treated with Ti and Zr compounds, the Cr treated aluminum plate is an aluminum plate treated with Cr compounds, the CP treated aluminum plate is an aluminum plate treated with a chromate-phosphate system, the hot water modified aluminum plate is an aluminum plate treated with hot water, the anodized aluminum plate is an aluminum plate treated with an anodizing process, and the surface treated steel plate is a steel plate obtained by a combination of one or more surface treatment processes including electroplating, Ti / Zr treatment, Cr treatment, CP treatment, hot water modification treatment and anodizing treatment. . An oxide film is formed on the surface of the above treated metal substrate to enhance the bonding strength with the coating.

[0053] S104: Take a composite film, the composite film including an adhesive layer and a polyolefin layer. Cover the composite film on at least one surface of the metal substrate, and make the side of the composite film with the adhesive layer face the metal substrate. The elongation at break of the polyolefin in the polyolefin layer is 300% to 800%.

[0054] S106: When the temperature of the composite film is 100°C to 180°C and the pressure is 0.1N / mm 2 Up to 10N / mm 2 The lamination is performed under the conditions of 0.001 second to 1 second. In an exemplary embodiment, the lamination temperature is 160° C. and the lamination pressure is 3 N / mm 2 , the lamination time is 0.02 seconds. In other exemplary embodiments, the lamination can be performed at 100°C to 180°C and a pressure of 0.1 N / mm 2 Up to 10N / mm 2 The lamination is carried out under the condition that the lamination time is 0.001 second to 1 second. The lamination can be carried out by roller pressing, but is not limited thereto. The lamination can also be carried out by mold pressing, bag pressing or other methods well known to those skilled in the art.

[0055] S108: After lamination, heat preservation is performed, and the heat preservation temperature is maintained at above 80°C for more than 1 second. After lamination, the temperature is maintained at above 80°C for more than 1 second so that the resin in the composite film laminated on the metal substrate has a uniform temperature distribution and a crystalline state. In an exemplary embodiment, the heat preservation temperature is maintained at 100°C for 3 seconds. In other embodiments, the heat preservation temperature is greater than 80°C and the heat preservation time is more than 1 second to make the resin in the composite film laminated on the metal substrate have a uniform temperature distribution and a crystalline state.

[0056] S110: Cooling, wherein the temperature is controlled below 60°C and maintained for more than 2 seconds. Cooling can be carried out in a water cooling tank, or by other cooling methods such as atmosphere cooling or those familiar to those skilled in the art. The cooling step can harden the melted and softened resin after heating to obtain a laminated material that can be used for a battery case. In an illustrative embodiment, the cooling temperature is maintained at 40°C and the cooling time is maintained for 2 seconds. In other embodiments, the cooling temperature is controlled below 60°C so that the melted and softened resin can be hardened.

[0057] The present invention selects the material composition of the composite film and cooperates with the above-mentioned laminate manufacturing process to enable the obtained laminate to adapt to the drawing process with a maximum drawing depth of 200 mm and avoid the defects of composite film breakage on the laminate and composite film peeling off from the metal substrate.

[0058] In an exemplary embodiment, before step S104, the following step is further included: applying an adhesive to at least one surface of the metal substrate, wherein the adhesive is one or more of an epoxy adhesive, a polyurethane adhesive, and an acrylic adhesive, so as to improve the bonding force between the composite film and the metal substrate.

[0059] In an exemplary embodiment, after step S110, the following steps are further included: heating at a temperature above 80°C for more than 1 second, and the heating is carried out by electric heating, hot air heating or roller heating. The heating can be carried out in a drying oven, thereby eliminating the stress difference of the composite film in the film thickness direction, reducing the crystallinity of the resin in the composite film, and thus improving the processing performance of the laminated material. After step S110, the obtained laminated material is heated to a temperature above 80°C and maintained for more than 1 second, and the obtained laminated material has better anti-fracture and anti-peeling properties than the laminated material that has not been heated.

[0060] Figure 2 FIG. 1 is a schematic structural diagram of an exemplary embodiment of a laminated material. The laminated material is manufactured by the method for manufacturing a laminated material provided by the present invention. Figure 2 As shown, the laminated material includes a metal substrate 10 and two composite films 20. In other exemplary embodiments, the number of the composite film 20 can also be one, that is, a single-side coating of the metal substrate 10. Each of the composite films 20 includes an adhesive layer 21 and a polyolefin layer 22. In the exemplary embodiment, the two composite films 20 of the metal substrate 10 can be the same or different, but both should include an adhesive layer 21 and a polyolefin layer 22. The thickness of each composite film 20 ranges from 17.5 μm to 150 μm.

[0061] The adhesive layer 21 covers the surface of the metal substrate 10. The adhesive layer 21 can be selected from one or more of EVA and its modified products, EAA and its modified products, polyolefin containing maleic anhydride, and polyester containing maleic anhydride. The adhesive layer 21 is mainly composed of a highly polar resin, which can form a chemical bond with the group on the surface of the metal substrate 10 to obtain reliable bonding. The adhesive layer 21 may also include other additives known to those skilled in the art. Preferably, the adhesive layer 21 is selected from one or more of EVA, polyethylene modified EVA, polypropylene modified EVA, EAA, polyethylene modified EAA, polypropylene modified EAA, polypropylene containing maleic anhydride, polyethylene containing maleic anhydride, polybutene containing maleic anhydride, polyethylene terephthalate containing maleic anhydride and polybutylene terephthalate containing maleic anhydride. More preferably, the adhesive layer 21 is selected from one or more of EVA, EAA, PE modified with maleic anhydride or maleic acid and PP modified with maleic anhydride or maleic acid.

[0062] The polyolefin layer 22 is located on the surface of the adhesive layer 21 away from the metal substrate 10. The polyolefin layer 22 is mainly composed of polyolefins. The polyolefin layer 22 may also include other additives well known to those skilled in the art. Polyolefin generally refers to a general term for a class of thermoplastic resins obtained by polymerizing or copolymerizing α-olefins such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 4-methyl-1-pentene, and certain cycloolefins alone, which have the characteristics of low relative density, good chemical resistance, good water resistance, good mechanical strength, electrical insulation, etc. The polyolefin layer 22 is mainly composed of polyolefins such as polypropylene (PP) and polyethylene (PE) with a breaking elongation of 300% to 800% to ensure that the laminated material is adapted to a drawing process with a maximum drawing depth of 200 mm. In other exemplary embodiments, based on different application scenarios, the polyolefin layer can also be replaced by a layer whose main component is PET.

[0063] By coating the polyolefin layer 22 and the metal substrate 10 with an adhesive layer 21, the adhesion between the polyolefin layer 22 and the metal substrate 10 can be effectively improved, thereby avoiding the defect of the polyolefin layer 22 peeling off from the metal substrate 10 during the deep drawing process.

[0064] The composite film of the present invention can be obtained by coextrusion. The polymer coextrusion process is a processing technology that uses several extruders to supply different molten material streams respectively, and merges and coextrudes them in a composite die to obtain a multi-layer composite product. The coextrusion process can make multiple layers of materials with different properties compounded with each other during the extrusion process, so that the product has the excellent properties of several different materials.

[0065] The composite film 20 used in the present invention includes an adhesive layer 21 and a polyolefin layer 22. The material ratio is adjusted by calculating the thickness ratio of the two layers, and the desired composite film is obtained at one time through a co-extrusion process.

[0066] The deep drawing process is a common process for processing existing hard pack battery shells. It is a stamping process that uses a mold to press a flat blank into an open hollow part of various shapes, or further makes the pressed open hollow blank into an open hollow part of other shapes and sizes while the thickness remains basically unchanged. During the deep drawing process, at the moment when the metal substrate is stressed and drawn, the composite film is drawn along with the metal substrate. Therefore, the composite film should have tensile properties and bonding properties compatible with the metal substrate to adapt to the deep drawing process.

[0067] The present invention selects the material composition of the composite film and cooperates with the above-mentioned laminate manufacturing process to enable the obtained laminate to adapt to the drawing process with a maximum drawing depth of 200 mm and avoid the defects of composite film breakage on the laminate and composite film peeling off from the metal substrate.

[0068] The requirements of the deep drawing process with a small depth on the tensile properties of the metal substrate, the tensile properties of the composite film and the bonding properties are lower than those of the deep drawing process with a large depth. Therefore, it is natural that the laminated material provided by the present invention can adapt to the deep drawing process with any value of the drawing depth below 200 mm, and the composite film will neither break nor peel off from the metal substrate.

[0069] Figure 3 The structure diagram of another exemplary embodiment of a laminated material manufactured by the method for manufacturing a laminated material provided by the present invention is shown in FIG. Figure 3 In the exemplary embodiment shown, both composite films 20 of the laminate are Figure 2 A lubricating layer 23 is added to the laminated material shown. The lubricating layer 23 is mainly composed of polyolefin and lubricant, and is formed on the surface of the polyolefin layer 22 away from the adhesive layer 21. The lubricating layer 23 may also include other additives well known to those skilled in the art. In each composite film 20, the thickness ratio of the lubricating layer 23, the polyolefin layer 22 and the adhesive layer 21 is 3:4:3 to 1:8:1. Adding a lubricating layer 23 is beneficial to the rolled composite film to prevent adhesion during the lamination process and facilitate unwinding, and prevent the surface of the composite film from being damaged due to adhesion. In other exemplary embodiments, the lubricating layer 23 may also be absent. The polyolefin used to constitute the polyolefin layer 22 and the polyolefin used to constitute the lubricating layer 23 are the same material, selected from one or more of PP and PE. The lubricating layer 23 and the polyolefin layer 22 are made of the same material, which is beneficial to improving the compatibility of the lubricating layer 23 and the polyolefin layer 22, so that the lubricating layer 23 and the polyolefin layer 22 are closely combined without peeling, so that the laminated material can avoid the composite film from being delaminated during the subsequent deep drawing process, which is beneficial to improving the product quality of the laminated material. The lubricating layer 23 can be formed by a co-extrusion method, that is, the raw materials of the adhesive layer 21, the polyolefin layer 22 and the lubricating layer 23 are added to an extruder, and the three-layer composite film is prepared by co-extrusion at one time. The composite film 20 can also be prepared by forming the adhesive layer 21, the polyolefin layer 22 and the lubricating layer 23 into films and then compounding them.

[0070] In addition, Figure 3 In the exemplary embodiment shown, the composite film 20 located on the upper side of the metal substrate 10 further includes a barrier layer 25. The thickness of the barrier layer 25 is, for example, greater than 5 μm. The barrier layer 25 is composed of a gas permeability of 5 ml (m 2·day·Mpa) or less, such as ethylene-vinyl alcohol copolymer, and is formed between the polyolefin layer 22 and the lubricating layer 23. This gives the laminated material a strong barrier property to prevent small molecules in the battery electrolyte from penetrating to the outside. When the laminated material is used to manufacture a battery housing, the composite film 20 with the barrier layer 25 is arranged on the inner side of the battery housing and contacts the electrolyte when in use. The barrier layer 25 can improve the electrolyte corrosion resistance and oxygen barrier performance of the battery housing made of the laminated material.

[0071] The barrier layer 25 may be formed by coextrusion. The raw materials of the adhesive layer 21, the polyolefin layer 22, the barrier layer 25 and the lubricant layer 23 are added to an extruder and coextruded once to obtain a composite film. The barrier layer 25 may also be formed into a composite film by forming a single film and then compounding it with the adhesive layer 21, the polyolefin layer 22 and the lubricant layer 23.

[0072] Figure 4 This is a schematic structural diagram of another exemplary embodiment of a laminated material manufactured by the method for manufacturing a laminated material provided by the present invention. Figure 4 , and Figure 3 The laminate material shown is similar to Figure 3 The difference is that the composite film 20 located on the lower side of the metal substrate 10 includes an adhesive layer 21, a polyolefin layer 22 and a PET layer 24. The PET layer 24 covers the surface of the polyolefin layer 22 away from the adhesive layer 21. The PET layer 24 is mainly composed of modified PET, which may or may not contain a lubricant, and may also contain other additives known to those skilled in the art to facilitate the acquisition of various properties required for the laminated material. The PET layer is formed into a film by a method known to those skilled in the art. When the PET layer contains a lubricant, the lubricant is added to the PET raw material and the film is formed by a method known to those skilled in the art.

[0073] The added PET layer 24 is located at the outermost layer of the battery shell after the laminated material is formed into a battery shell. It can improve the insulation of the battery shell, has excellent scratch resistance, and makes it easy to bond the manufactured battery with other batteries with PET layers on the back to form a battery pack.

[0074] In the actual application of forming the laminated material into a battery housing, it is sometimes necessary to perform a treatment such as welding on the surface of the metal substrate 10. If the surface of the metal substrate 10 is covered with a composite film 20, the treatment effect will be affected. Therefore, during the processing of the laminated material, the area on the surface of the metal substrate 10 that is pre-treated should not be covered by the composite film 20. The method we adopted is to cut the composite film 20 before covering the composite film 20 on the metal substrate 10, as described below.

[0075] Figure 5 Schematic diagram for explaining the use of a die-cutting die to cut a composite film. Figure 5 , firstly, the side of the composite film 20 away from the adhesive layer 21 is attached to a substrate film 30. Then, the die-cutting die 40 is used to cut off the part of the composite film 20 corresponding to the pre-treated area of ​​the metal substrate 10 surface while the substrate film 30 remains intact, leaving several rectangular film blocks 26 still attached to the substrate film 30. However, it is not limited to this. The film block 26 can be a film sheet of a specific shape. The specific shape of the film sheet depends on the shape of the battery shell of the final product. The film sheet 26 can be a continuous whole. Then, the film block 26 attached to the substrate film 30 is covered on the metal substrate 10, and the substrate film 30 will eventually be removed when the laminated material is rolled up, or it can be removed when the laminated material is used. In this way, the pre-treated area on the surface of the metal substrate 10 will not be covered by the composite film 20. Among them, the size and shape of the die-cutting die are determined according to the actual application scenario. The substrate film is a release PET, a release paper or a release non-woven fabric. The release effect of the substrate film can be obtained by coating a release coating on the surface of the substrate film.

[0076] In the exemplary embodiment, the composite film cutting process is specifically as follows: take the composite film roll and the substrate film roll, adhere the side of the composite film 20 away from the adhesive layer to the substrate film 30, and while the composite film 20 and the substrate film 30 are conveyed stepwise along the feeding direction F, use the die-cutting die 40 to cut the composite film 20 but ensure that the substrate film 30 is intact. The composite film 20 is cut into a plurality of discontinuous rectangular film blocks 26 adhered to the substrate film, and the remaining composite film after cutting is rolled up. The substrate film with the plurality of rectangular film blocks attached is rolled up to obtain the composite film after cutting.

[0077] The composite film is cut by a die-cutting die, wherein the size and shape of the die-cutting die cutter can be designed according to the actual application scenario. The distribution spacing between the individual film blocks can be adjusted according to the actual application requirements by adjusting the stepping distance of the feeding device and the cutter spacing of the die-cutting die, so that the size, shape and distribution of the cut composite film that meets the application conditions can be obtained.

[0078] The method of manufacturing a laminated material using the cut composite film is the same as the method of manufacturing a laminated material using the uncut composite film. After the laminated material is manufactured, it is directly rolled up and stored. When the laminated material is rolled up, the substrate film can also be peeled off at the same time, and the substrate film can be rolled up and recycled.

[0079] Through the above steps, after the surface of the metal substrate is coated with the composite film, a portion of the metal substrate can be exposed to facilitate subsequent operations such as welding.

[0080] The following specifically describes the method of manufacturing a laminated material through Examples 1-11 and Comparative Examples 1-2, and the method of manufacturing a battery housing by using the obtained laminated material through a deep drawing process.

[0081] Embodiment 1:

[0082] 1) According to Figure 1 The method for manufacturing the laminated material is shown

[0083] S102: Take a metal substrate with a thickness of 1.0 mm, and the metal substrate is an aluminum substrate with a grade of AL3003.

[0084] S104: Take two composite films, namely composite film I and composite film II, each composite film includes a lubricating layer composed of LLDPE and a lubricant, a polyolefin layer composed of LLDPE, and a PE adhesive layer containing 6% maleic anhydride, wherein the thicknesses of the lubricating layer, the polyolefin layer, and the adhesive layer are 30 μm, 40 μm, and 30 μm, respectively. Cover the two surfaces of the metal substrate respectively with the two composite films, and make the side of the composite film provided with the adhesive layer face the metal substrate.

[0085] S106: The temperature of the composite film is 160°C and the pressure is 3N / mm 2 The lamination was carried out under the conditions of , and the lamination time was 0.02 seconds.

[0086] S108: After lamination is completed, heat preservation is performed, and the heat preservation temperature is maintained at 100° C. for 3 seconds.

[0087] S110: Cooling, wherein the temperature is controlled at 40°C and maintained for 2 seconds, thereby obtaining a laminated material.

[0088] 2) Manufacturing battery casing

[0089] The obtained laminated material is unrolled and put into a punch press. After several punchings, a semi-finished product is obtained. During the punching process, the short side stretching ratio or the stretch thinning ratio is controlled. After the semi-finished product is trimmed and cleaned, a battery shell with a drawing depth of 90 mm is obtained. The maximum value of the short side stretching ratio is controlled to be 1:6, and the short side stretching ratio is the ratio of the short side length at the bottom of the battery shell to the height of the battery shell. The maximum value of the stretch thinning ratio is controlled to be 60%, and the stretch thinning ratio is the percentage of the thickness of the laminated material thinned after stretching to the thickness of the laminated material before stretching.

[0090] Examples 2-11 and Comparative Examples 1-2 are examples after adjusting the components and process parameters listed in Table 1 based on Example 1.

[0091] Table 1 also shows the drawing results of the laminated materials of various embodiments and comparative examples during the process of making battery casings.

[0092] Table 1

[0093]

[0094]

[0095]

[0096]

[0097]

[0098] ○: The film is not broken and peeled off *: The film is broken and peeled off

[0099] Note: The main component of the lubricant in Table 1 is silicon dioxide.

[0100] The metal substrate AL3003 in the above embodiment is replaced by an aluminum plate that has been pre-treated with Ti / Zr, an aluminum plate that has been treated with Cr, an aluminum plate that has been treated with CP, an aluminum plate that has been treated with hot water modification, an anodized aluminum plate, or a surface-treated steel plate. The surface-treated steel plate is a steel plate obtained by a combination of one or more surface treatment processes including electroplating, Ti / Zr treatment, Cr treatment, CP treatment, hot water modification treatment, and anodizing treatment. The composite film in the battery shell will not break or peel off.

[0101] In summary, the present invention selects the material composition of the composite film and cooperates with the above-mentioned laminated material manufacturing process to enable the obtained laminated material to adapt to the drawing process with a drawing depth of 120mm to 200mm and avoid the defects of the composite film on the laminated material breaking and the composite film peeling off from the metal substrate.

[0102] It should be understood that although this specification is described according to various embodiments, not every embodiment contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

[0103] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation scheme or changes that do not deviate from the technical spirit of the present invention, such as combination, division or repetition of features, should be included in the scope of protection of the present invention.

Claims

1. A method for producing a laminate, characterized in that The following steps are involved: A metal substrate (10) having a thickness of 0.12 mm to 2.0 mm is obtained; A composite film (20) is taken, wherein the composite film (20) comprises an adhesive layer (21) and a polyolefin layer (22), and the composite film (20) is covered on at least one surface of the metal substrate (10), and the side of the composite film (20) provided with the adhesive layer (21) faces the metal substrate (10), and the elongation at break of the polyolefin in the polyolefin layer (22) is 300% to 800%; The temperature of the composite membrane (20) is 100°C to 180°C and the pressure is 0.1 N / mm 2 Up to 10N / mm 2 Lamination is performed under the conditions of , and the lamination time is 0.001 second to 1 second; After lamination, heat preservation is performed, and the heat preservation temperature is maintained above 80°C for more than 1 second; and Cooling, wherein the temperature is controlled below 60°C for more than 2 seconds.

2. The method according to claim 1, characterized in that Before the step of covering the composite film (20) onto at least one surface of the metal substrate (10), the method further comprises the following steps: An adhesive is applied to at least one surface of the metal substrate (10) to be covered by the composite film (20), wherein the adhesive is one or more of an epoxy adhesive, a polyurethane adhesive and an acrylic adhesive.

3. The method according to claim 1, characterized in that After the cooling step, the following steps are also included: The heating is performed at a temperature of 80° C. or higher for more than 1 second, wherein the heating is performed by electric heating, hot air heating or roller heating.

4. The method according to claim 1, characterized in that The adhesive layer (21) comprises one or more of EVA and its modified products, EAA and its modified products, polyolefin containing maleic anhydride and polyester containing maleic anhydride.

5. The method according to claim 1, characterized in that The composite film (20) has a thickness of 17.5 μm to 150 μm.

6. The method according to claim 1, characterized in that The composite film (20) further comprises a lubricating layer (23), wherein the lubricating layer (23) comprises polyolefin and a lubricant, and the lubricating layer (23) is formed on a side of the polyolefin layer (22) facing away from the adhesive layer (21). In the composite film (20), the thickness ratio of the lubricating layer (23), the polyolefin layer (22) and the adhesive layer (21) is 3:4:3 to 1:8:

1.

7. The method according to claim 6, characterized in that The composite film (20) further comprises a barrier layer (25), the thickness of the barrier layer (25) being greater than 5 μm, and the air permeability of the barrier layer (25) being 5 ml (m 2 ·day·Mpa) or less, and is formed between the polyolefin layer (22) and the lubricating layer (23).

8. The method according to claim 7, characterized in that The polyolefin contained in the polyolefin layer (22) and the lubricating layer (23) is the same and is selected from one or more of PP and PE. When the oxygen permeability is 90%RH, the air permeability is 5ml (m 2 The resin with a density of 1000 ·day·Mpa) or less is ethylene-vinyl alcohol copolymer.

9. The method according to claim 1, characterized in that The composite film (20) further comprises a PET layer (24), wherein the PET layer (24) covers the side of the polyolefin layer (22) facing away from the adhesive layer (21).

10. The method according to claim 9, characterized in that The PET layer (24) and the polyolefin layer (22) are connected via an adhesive.

11. The method according to any one of claims 1 to 10, characterized in that Also includes: Before the composite film (20) is covered on the metal substrate (10), the side of the composite film (20) facing away from the adhesive layer (21) is adhered to a substrate film (30), and the composite film (20) is cut into continuous and / or discontinuous film blocks (26) using a die-cutting die while keeping the substrate film (30) intact.

12. The method according to claim 11, characterized in that The substrate film (30) is release PET, release paper or release non-woven fabric.

13. The method according to claim 1, characterized in that The metal substrate (10) is selected from one of an untreated aluminum plate, an aluminum plate pre-treated with Ti / Zr, an aluminum plate treated with Cr, an aluminum plate treated with CP, an aluminum plate treated with hot water modification, an anodized aluminum plate and a surface-treated steel plate. The surface-treated steel plate is a steel plate obtained by a combination of one or more surface treatment processes selected from electroplating, Ti / Zr treatment, Cr treatment, CP treatment, hot water modification and anodizing.

14. Use of the laminate produced according to the method of any one of claims 1 to 13 for producing a battery casing.

15. The use according to claim 14, characterized in that The laminated material is used for manufacturing a battery housing by a deep drawing process, wherein the deep drawing depth of the deep drawing process is 120 mm to 200 mm.